A Study of δ-Globin Gene Mutations in the UK Population: Identification of Three Novel Variants and Development of a Novel DNA Test for Hb A′2. (June 2014) - Khalil, Mohamed S. M.; Marouf, Samy; Element, David; Timbs, Adele; Gallienne, Alice; Schuh, Anna; Old, John M.; Henderson, Shirley
Abstract We report here the spectrum of δ-globin gene mutations found in the UK population. Nine different δ chain variants and two δ-thalassemia (δ-thal) mutations were characterized in a study of 127 alleles in patients with either a low Hb A2 value or a split Hb A2 peak on high performance liquid chromatography (HPLC). The most common δ chain variant was Hb <![CDATA[ opagenumbers A_2' ]]> (or Hb B2) [δ16(A13)Gly → Arg; HBD: c.49G > C] (77.0%), followed by Hb A2-Yialousa [δ27(B9)Ala → Ser; HBD: c.82G > T] (12.0%), Hb A2-Babinga [δ136(H14)Gly → Asp; HBD: c.410G > A] (3.0%), Hb A2-Troodos [δ116(G18)Arg → Cys; HBD: c.349C > T] (1.0%), Hb A2-Coburg [δ116(G18)Arg → His; HBD: c.350G > A] (2.0%) and Hb A2-Indonesia [δ69(E13)Gly → Arg; HBD: c.208G > C] (1.0%). Three novel variants were identified: Hb A2-Calderdale [codon 2 (CAT > AAT), His → Asn; HBD: c.7C > A], Hb A2-Walsgrave [codon 52 (GAT > CAT), Asp → His; HBD: c.157G > C] and Hb A2-St. George's [codon 81 (CTC > TTC), Leu → Phe; HBD: c.244C > T]. In addition, two known δ-thal mutations were observed: −68 (C > T); HBD: c.-118C > T and codon 4 (ACT > ATT); HBD: c.14C > T. Amplification refractory mutation system (ARMS) primers were developed to provide a simple molecular diagnostic test for the most common variant, Hb <![CDATA[ opagenumbers A_2' ]]> . Three of the variants had a characteristic HPLC retention time that can be used for a presumptive diagnosis.